Analysis of the Level of Satisfaction Among Residents of Cirebon City with Electronic Services - Desi Maelinda; Siti Khumayah (Al-Makki Publisher, 2026)
This study aimed to analyze the level of public satisfaction with electronic-based public services through the Sedulur Portal in Cirebon City. The research employed a descriptive method with a qualitative approach to explore the perceptions and experiences of users of the Sedulur Portal. Data were collected through in-depth interviews, observations, and documentation involving informants from the Cirebon City Communication, Informatics, and Statistics Office (Dinas Komunikasi, Informatika, dan Statistik, DKIS), Sedulur Portal operators, and residents who utilized the Sedulur Portal digital services. Service quality analysis was based on the five dimensions of the Servqual model: tangibles, reliability, responsiveness, assurance, and empathy. The findings showed that digital services were perceived as relatively good in terms of interface simplicity, system reliability, and security and trust as official government services. However, limitations in the available features of the Sedulur Portal affected responsiveness and personalized service aspects, which remained suboptimal. This study recommends developing additional features to support social improvement, enhance two-way communication, and strengthen system performance to improve the quality and accessibility of Sedulur Portal digital services.